TEACHING NOTE: We Built It, Now Will They Come? bOK Systems Corp. - Ensign, Prescott C.; Mirzaee, Aydin Y. (Senate Hall, 2015)
SYNOPSIS: bOK Systems Corp., a Canadian start-up based in Ottawa, Ontario, has successfully been able to develop and test its product in the market but is looking to 'take it to the next level' and increase the adoption of its service amongst the masses. The team is facing challenges such as a lack of time and money; if only Aydin Mirzaee and his venture team could devote their entire energy and attention to the company. Two of the main developers (Aydin's brother Amin Mirzaee and Samuel Cormier Iijima) are full-time undergraduate students at McGill University, the other one (Pooya Eslamdoust) is studying at Humber College (see Case Appendix A). Aydin himself is a full-time employee at a large multinational telecommunications company-which is how the company is currently funded. It is October 2007 and the venture team has several dilemmas to work through. Among them, it is having trouble raising money for its venture partially because of the lacklustre investment climate in Canada and the competitive environment overall. The team is considering multiple alternatives that are detailed below-such as focusing full-time on bOK (i.e., quitting all other efforts), bringing in an external CEO, moving away from offering the service/product for free, to outright sale or abandonment of the venture.